A systematic review of authorial voice construction in scientific discourse - Abdug‘aniyeva, Zebuniso (The Lingua Spectrum, 2025)
This critical review article examines authorial voice in scientific discourse, employing Hyland’s interaction model as an analytical framework. The study identifies linguistic units that constitute authorial voice in scholarly texts and analyzes contextual variables influencing its manifestation. Within scientific discourse, authorial voice is constructed through stance and engagement markers, with disciplinary domains, genres, and cultural contexts potentially having significant influence on it. While the interaction model provides valuable insights into sentence-level authorial voice features, it does not comprehensively address the broader textual dimensions of authorial voice. This article proposes an integrated methodological approach for such analysis and offers pedagogical implications. This approach may have particular relevance for non-native English writers navigating scientific discourse conventions. The review contributes to our understanding of how scholars bring forth their discursive presence despite the epistemological and rhetorical constraints of scientific communication.